PENGARUH KEADILAN PROSES SELEKSI DAN NEGOSIASI GAJI TERHADAP DAYA TARIK ORGANISASI DENGAN REPUTASI PERUSAHAAN SEBAGAI VARIABEL MEDIASI - Pratama, Octavianus Sumardana; Rahyuda, Agoes Ganesha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.04.TAHUN 2018DO - 10.24843/EEB.2018.v07.i04.p08, 2018)
The importance of organizational attractiveness management, attract potential job applicants who have superior competence and it suitables with the needs of the organization.  The company realized that the way in getting potential employee candidates was made a fair selection procedure for prospective employees. Salary negotiation becomes an inseparable aspect in the recruitment process. Therefore, the organization needs attention to the ways in which potential employee candidates view salary negotiations as a organizational attractiveness. The factors as well as the selection fairness and the salary negotiations that the company has made will improve the firm reputation and it certainly attract interest in applying for jobs. The sample were 53 respondents from permanent and non-permanent teachers at kindergarten, elementary, junior, and senior high school of Santo Yoseph Denpasar by using proportional sampling technique. This research used analysis technique PLS (Partial Least Square). The results showed that the selection fairness and the salary negotiation had a positive and significant impact on the firm reputation. Furthermore, they had a positive and significant influence on the organizational attractiveness. Besides that, the firm reputation as a mediating variable had a positive and significant impacts to the selection fairness and the salary negotiation on the organizational attractiveness.